Laboratórios do Departamento de Odontologia Infantil e Social - Teodoro Filho, Ilídio; Fernandes, Maria dos Santos Ferreira; Silva, Mário Luis da; Souza, Nilton César; Rosa, Valderez Freitas (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Ilídio Teodoro Filho Maria dos Santos Ferreira Fernandes Nilton César Souza